Environmental Sociology : European Perspectives and Interdisciplinary Challenges - Heinrichs, Harald (Dordrecht : Springer Science+Business Media B.V., 2010., 2017)
Chapter 1: Introduction: New Trends and Interdisciplinary Challenges in Environmental Sociology. Chapter 2:Social Theories of Environmental Reform: Towards a Third Generation. Chapter 3: The New Climate Change Discourse: A Challenge for Environmental Sociology. Chapter 4: Earth System Governance and the Social Sciences. Chapter 5: Ecological Regimes: Towards a Conceptual Integration of Biophysical Environment into Social Theory. Chapter 6: Understanding Responses to the Environmental and Ethical Aspects of Innovative Technologies: The Case of Synthetic Biology in Europe. Chapter 7: Social Simulation: A Method to Investigate Environmental Change from a Social Science Perspective. Chapter 8: Trust and Cooperation as Requirements for Maintaining Environmental Governance Capacity. Chapter 9: Rational Choice Theory and the Environment: Variants, Applications, and New Trends. Chapter 10: Environmental Knowledge and Deliberative Democracy. Chapter 11: Knowledge and Social Learning for Sustainable Development. Chapter 12: Beyond Neocorporatism? Transdisciplinary Case Studies as a Means for Collaborative Learning in Sustainable Development. Chapter 13: Social Practices and Sustainable Consumption: Benefits and Limitations of a New Theoretical Approach. Chapter 14: (Im)mobility and Environment–Society Relations: Arguments for and Against the ‘Mobilisation’ of Environmental Sociology. Chapter 15: Environmental Sustainability as Challenge for Media and Journalism. Chapter 16: The Experimental Turn in Environmental Sociology: Pragmatism and New Forms of Governance. Chapter 17: Risk, Society and Environmental Policy: Risk Governance in a Complex World. Chapter 18: Climate Change and Society – Communicating Adaptation. Chapter 19: Moving Ahead: Environmental Sociology’s Contribution to Inter- and Transdisciplinary Research.